The importance of systematic management in ensuring economic and financial stability - Akramova Aziza Abduvohidovna (Genius Publishing Group, 2023)
In this article, the importance of systematic management in ensuring economic and financial stability, the ways of using modern management and the conditions for achieving efficiency of management are mentioned.
Keywords: Systematic management; financial stability; modern management